Role of Sputum Examination in Tuberculous Pleural Effusion Patients at Zagazig University Hospitals - Niveen E. Zayed, Marwa H. Mohamed, Adel H. A. Ghoneim, Mohamed M. N. AboZaid; Malek, Mai (International Journal of Innovative Research in Medical Science, 2017)
Background: Tuberculous pleuritis should be considered in any patient with an exudative pleural effusion. In most cases of tuberculous pleural effusion there are no apparent parenchymal lung lesions on chest radiography. Spontaneous or induced sputum specimen examination for acid fast bacilli (AFB) is important for such cases. Parenchymal lesion including focal areas of subpleural cavitation and lymphadenopathy can be visualized with the use of computed tomography, which is not apparent on routine chest radiography. In such cases there is possibility of isolation of tubercle bacilli in sputum which can be indicator of infectiousness. Aim of the Study: To evaluate the role of sputum examination for (AFB) in tuberculous pleural effusion cases as indicator for infectiousness. Subjects and Methods: The present study included 64 Patients proved to have tuberculous pleural effusions, 32 patients with parenchymal lesions and 32 patients without parenchymal lesion. The diagnosis of tuberculous pleural effusion is performed by direct smear examination and culture of pleural fluid, pleural biopsy examination for AFB, culture and presence of caseating granuloma, and ADA examination of pleural fluid. Sputum examination for AFB was done by: Direct smear examination on 3 consecutive days and Culture of on Lowenstein-Jensen (L-J) media. Results: Sputum Z-N examination for AFB was positive for tuberculosis in 7 out of 32 cases (21.9%) in patients with apparent radiologic parenchymal infiltrate and in 2 out of 32 cases (6.3%) in patients with no apparent radiologic parenchymal infiltrate in which tuberculous etiology was confirmed by histology and /or bacteriology. Sputum culture on L-J media was positive for mycobacterium tuberculosis growth in 13 out of 32 cases (40.6 %) in patients with apparent radiologic parenchymal infiltrate and in 7 out of 32 cases (21.9%) in patients with no apparent radiologic parenchymal infiltrate. Conclusion: Sputum examination for AFB in cases of tuberculous pleural effusion remain doubtful but it may show important benefit in diagnosis, treatment of such cases and as an indicator of infectiousness